Identification of the Fcα/μR isoform specifically expressed in the kidney tubules - Kurita, Naoki; Honda, Shin-ichiro; Usui, Kenta; Shimizu, Yoshio; Miyamoto, Akitomo; Tahara-Hanaoka, Satoko; Shibuya, Kazuko; Shibuya, Akira (Molecular immunology, 2009)
Fcα/μR is expressed not only in lymphoid, but also in non-lymphoid organs, including kidney. However, molecular and functional characteristics of Fcα/μR, particularly expressed in non-lymphoid organs, have remained unclear. Here we identified an isoform of Fcα/μR in the murine kidney on the C57BL/6J background. The kidney expressed only the isoform, which was not expressed in other lymphoid and non-lymphoid organs, and this isoform binds both IgA and IgM. Immunohistochemical analyses suggested that the Fcα/μR isoform was expressed in the tubular epithelial cells, but not in the glomeruli. This was confirmed by flow cytometry analysis of isolated tubular epithelial cells and by RT-PCR analyses using the separately excised glomerular and tubular regions by the laser microdissection system. These results suggest that Fcα/μR may not be involved in IgA deposition in glomerular mesangium cells in IgA nephropathy. Rather, it may play an important role in immunity in the renal tubular regions.